American standard code for information interchange mapping technique for text hiding in the RGB and gray images - Ahmed Abdulrudah Abbass; Salam Al-augby; Hussein Lafta Hussein; Jasim Hussein Kaabi; Robert Tornai (Institute of Advanced Engineering and Science, 2022)
One of the significant techniques for hiding important information (such as text, image, and audio) is steganography. Steganography is used to keep this information as secret as possible, especially the sensitive ones after the massive expansion of data transmission through the Internet inside a conventional, non-secret, file, or message. This paper uses the American standard code for information interchange (ASCII) mapping technique (AMT) to hide the data in the color and grey image by converting it in a binary form, also convert the three levels of the red, green, and blue (RGB) image and grey image in the binary form, and then hide the data through hiding every two bits of the text in the two bits of one of the levels from the RGB image and grey image that means the text will be distributed throughout the images and allows hiding large amounts of data. That will send the information in a good securing way.